A Systematic Review on the Clinical Outcomes of Dipeptidyl Peptidase-4 Inhibitors in Type 2 Diabetes Mellitus Patients - Rodrigues, Prudence A.; Samuel, Ndayishimye (Indian Journal of Pharmacy Practice)
Context: clinical outcomes of Dipeptidyl Peptidase-4 inhibitors can be beneficial for the patients in controlling high blood sugar it can also cause potential adverse effects Aim: The main objective of this study was to assess the risks and benefits of Dipeptidyl peptidase-4inhibitors (DPP-4I) in type 2 diabetes mellitus patients. Method: systematical articles on Dipeptidyl peptidase-4 inhibitors were reviewed from the year 2015 up to 2017 from 3 databases such as: EMBASE, COCHRANE and MEDSCAPE and some diabetes associations, the main such were: DPP-4 inhibitor, incretin, type 2 diabetes mellitus, Vildagliptin, Sitagliptin, Linagliptin, Saxagliptin, Alogliptin, 69 citations were included after screening for duplication and biased articles. Results: All DPP-4I are efficacious for improving blood glucose level among type 2 diabetes mellitus patients without causing hypoglycemic effects, and they can be used as monotherapy or in combination with other antidiabetic agents, Linagliptin offer uniqueness properties due to its non-renal excretion it improves microalbuminuria, whereas remaining DDP-4I cause a marginal changes on renal function, there is no hepatotoxicity among the DPP-4I no dose adjustment for Linagliptin, Sitagliptin, saxagliptin due non-hepatic excretion, only dose reduction is required for patients with minor hepatic functional impairment taking Vildagliptin and saxagliptin due to their partially elimination via liver,DPP-4I also protect patients for cardiovascular complications due its ability of reducing or maintaining the stability of body weight and lipid profile. They also show a low risk for increasing pancreatitis among T2DM and the others side effect were comparable less when compared to other anti-hyperglycemic agents. Conclusion: DPP-4I significantly control blood sugar level by decreasing glycated hemoglobin, fasting blood sugar, random blood sugar and they are not associated with hypoglycemic events they also minimize cardiovascular complications by reducing fats and weight in type 2 diabetes mellitus patients, in addition DPP-4I helps in renal and liver protection. Over all, DPP-4I reduce morbidity and mortality rate among T2DM patients.
Keywords: DPP-4I; T2DM; Incretin; Saxagliptin; Linagliptin; Sitagliptin; Vildagliptin; Alogliptin.